2019
DOI: 10.1080/09638288.2018.1554008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing lower limb position sense in stroke using the gradient discrimination test (GradDT™) and step-height discrimination test (StepDT™): a reliability and validity study

Abstract: Purpose: To evaluate the psychometric properties of two novel tests of lower limb position sense. Methods: Our newly developed tests assess discrimination thresholds of underfoot slope and step height perception using a two alternative forced choice approach. Stroke participants (n=32) and age matched controls (n=32) were tested. Inter-and intra-rater reliability and agreement, sensitivity and specificity, discriminant and convergent validity were evaluated. Results: Intra-rater reliability for both variants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…The GradDT evaluates sensory–perceptual ability to discriminate underfoot surface gradient or slope during standing. It has been described previously and shown to be reliable and valid in a stroke population . It uses a 2–alternative forced choice paradigm, in which 2 differing sloping platforms, a base and a comparator, are mentally compared (discriminated).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The GradDT evaluates sensory–perceptual ability to discriminate underfoot surface gradient or slope during standing. It has been described previously and shown to be reliable and valid in a stroke population . It uses a 2–alternative forced choice paradigm, in which 2 differing sloping platforms, a base and a comparator, are mentally compared (discriminated).…”
Section: Methodsmentioning
confidence: 99%
“…The StepDT uses the 2–alternative forced choice paradigm approach as detailed previously and has been described and psychometrically evaluated previously in stroke . This test assesses an individual's ability to discriminate the height of a step, through lower limb position sense, without visual feedback.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also reported that perception impairment worsens over time in stroke patients [ 13 , 14 ], and 25–75% of such patients require assistance to perform daily activities [ 15 , 16 ]. Therefore, appropriate measurements that evaluate deficits in muscle perceptions using active joint reproduction tests in ankle movements are crucial and could provide true reflections of functional performances of the ankle joint during daily activities in post-stroke patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eine besondere Bedeutung in der Verarbeitung sen sorischer Information wird dabei dem Thalamus zugespro chen, der als Schaltstation zwischen afferenten Leitungs bahnen und der Großhirnrinde gilt [16]. [6,8,9]. Bevor eine Testung durchgeführt wird, soll te aber nicht nur klar sein, welche der oben genannten Sinnesmodalitäten man adressiert, sondern auch, welcher Aspekt der jeweiligen Sinnesmodalität untersucht werden soll.…”
unclassified